Five new species of freshwater crabs of the genera Ghatiana Pati & Sharma, 2014, and Gubernatoriana Bott, 1970 (Crustacea, Decapoda, Brachyura: Gecarcinucidae Rathbun, 1904) from the Western Ghats, India - Pati, S.k.; Thackeray, T.; Khaire, A. (Zootaxa, 2016)
Five new species of gecarcinucid freshwater crabs, Ghatiana atropurpurea n. sp., Ghatiana splendida n. sp., Gubernatoriana alcocki Pati n. sp., Gubernatoriana thackerayi Pati n. sp., and Gubernatoriana waghi Pati n. sp. are described from the Western Ghats in Maharashtra and Goa states of India. Ghatiana atropurpurea n. sp. can be differentiated from other species of Ghatiana Pati & Sharma, 2014 by the shape and colour of its carapace, and the sigmoid-shaped male first pleopod (G1). Ghatiana splendida n. sp. is separated from its congeners mainly by its long anterolateral margin of the carapace and short terminal article of the G1. Besides, the colour pattern (deep pink carapace and chelipeds, orange ambulatory legs) of G. splendida n. sp. is exceptional among its congeners. Gubernatoriana alcocki n. sp. is unique among species of Gubernatoriana Bott, 1970 due to its inwardly curved tip of the terminal article of the G1. The stout and cone-shaped terminal article of the G1 of G. thackerayi n. sp. is characteristic among its congeners. In addition, G. thackerayi n. sp. has a unique colouration amongst congeners (violet-red carapace and ambulatory legs, orange-red chelipeds). Gubernatoriana waghi n. sp. can be distinguished from its congeners by the quadrate-shaped carapace, narrow frontal margin, pointed tips of the cheliped fingers, short terminal article of the G1 and very short or vestigial terminal article of the male second pleopod (G2). The body colour (burnt orange carapace and ivory coloured chelipeds and ambulatory legs) of G. waghi n. sp. is also important to distinguish live crabs of the genus. Key to the species of Ghatiana and Gubernatoriana is provided.